2022
DOI: 10.1038/s41467-022-30733-6
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical micro/nanostructured silver hollow fiber boosts electroreduction of carbon dioxide

Abstract: Efficient conversion of CO2 to commodity chemicals by sustainable way is of great significance for achieving carbon neutrality. Although considerable progress has been made in CO2 utilization, highly efficient CO2 conversion with high space velocity under mild conditions remains a challenge. Here, we report a hierarchical micro/nanostructured silver hollow fiber electrode that reduces CO2 to CO with a faradaic efficiency of 93% and a current density of 1.26 A · cm−2 at a potential of −0.83 V vs. RHE. Exceeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…80 In another study, a Cu 6 Sn 5 phase was prepared to cover the Cu-HFGDE, and a >80% FE to formate was obtained at 400 mV, which outperformed most of the other Sn-based GDE with a better microenvironment for triple-phase interfaces. 81 When Ag nanoparticles were used to prepare the HFGDE, a Faradaic efficiency of 93% and a current density of 1.26 A cm −2 at a potential of −0.83 V was reported for the CO 2 electroreduction to CO. 82 The location of an electrocatalytic reaction on a CL in a GDE is an important issue and any false reasoning would affect the novel electrocatalysis design studies for CO 2 electroreduction. The debate about whether a triple-phase boundary exists in a CL is an old one.…”
Section: Superhydrophobic and Superaerophilic Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…80 In another study, a Cu 6 Sn 5 phase was prepared to cover the Cu-HFGDE, and a >80% FE to formate was obtained at 400 mV, which outperformed most of the other Sn-based GDE with a better microenvironment for triple-phase interfaces. 81 When Ag nanoparticles were used to prepare the HFGDE, a Faradaic efficiency of 93% and a current density of 1.26 A cm −2 at a potential of −0.83 V was reported for the CO 2 electroreduction to CO. 82 The location of an electrocatalytic reaction on a CL in a GDE is an important issue and any false reasoning would affect the novel electrocatalysis design studies for CO 2 electroreduction. The debate about whether a triple-phase boundary exists in a CL is an old one.…”
Section: Superhydrophobic and Superaerophilic Surfacesmentioning
confidence: 99%
“…CO 2 gas was purged through the inner side of the HFGDE and the outer surface acts as catalytic sites at three-phase boundaries during the CO 2 electroreduction. 79–82 Faradaic efficiencies of CO 2 to CO reduction up to 85% were obtained at overpotentials between 200 and 400 mV. 79 High selectivity for CO 2 electroreduction to formate with a maximum FE of 77.1% at a high current density of 34.7 mA cm −2 was obtained due to the formation of a high CO 2 partial pressure in the cathode pores.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 Furthermore, we achieved efficient formation of CO at ampere level current density (>1 A cm −2 ) by optimizing the surface structure of a Ag hollow fiber. 32 The forced mass transfer of the hollow fiber enables the continuous transport of CO 2 to the catalyst surface and enhances the formation of a three-phase interface between CO 2 , electrode, and electrolyte, thus achieving ultra-high current density. Extensive studies have confirmed that hollow-fiber GPEs exhibit compelling performance for a stable eCO 2 RR at industrial-scale current density.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The hierarchical core-shell/yolk-shell/hollow (CS/YS/Ho) structure has been studied in depth because of the controllable structure and large specific surface area. [14][15][16] Therefore, they are widely used in sensing, 17 drug delivery, 18 photocatalysis/electrocatalysis, 19,20 and electrochemical energy storage. 21,22 The traditional strategy for the CS/YS/Ho structure is mainly focused on the template method and demands multiple synthesis steps.…”
Section: Introductionmentioning
confidence: 99%